1993
DOI: 10.1111/j.1365-2222.1993.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Down modulation of L‐Selectin expression on eosinophils recovered from bronchoalveolar lavage fluid after allergen provocation

Abstract: In allergic asthma eosinophils infiltrate into the lung after allergen challenge. The mechanism of this cellular infiltration is not fully understood. L-Selectin is involved in leucocyte-endothelial cell recognition and participates in homing of leucocytes into sites of inflammation. To find indications for a role of L-Selectin in the migration of eosinophils to the bronchoalveolar space we measured L-Selectin expression on eosinophils in peripheral blood and bronchoalveolar lavage fluid (BAL) 4 hr after the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 41 publications
(57 reference statements)
2
15
1
1
Order By: Relevance
“…These data suggest that expression of am/CD11b and L-selectin/CD62L is controlled differently compared with the modulated expression of these markers on cells activated in vitro (Fig 1, F) 39,40 or in the lung tissue in vivo. 47 Our data are consistent with a model that am bright /L-selectin bright cells comprise a phenotype that facilitates adhesion and homing in allergic asthmatic subjects. During subsequent extravasation, Lselectin is shed from the surface, whereas am is even more increased.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that expression of am/CD11b and L-selectin/CD62L is controlled differently compared with the modulated expression of these markers on cells activated in vitro (Fig 1, F) 39,40 or in the lung tissue in vivo. 47 Our data are consistent with a model that am bright /L-selectin bright cells comprise a phenotype that facilitates adhesion and homing in allergic asthmatic subjects. During subsequent extravasation, Lselectin is shed from the surface, whereas am is even more increased.…”
Section: Discussionsupporting
confidence: 91%
“…CD29 is a member of the very-late-activation integrin family and known to function as an adhesion and signaling molecule. CD62L (L-selectin) plays a critical role in initiating the interactions of cells with the activated endothelium at an inflammatory site and is characteristically down-modulated in response to cell activation (6,16,19). Increased CD29 and decreased CD62L levels were also observed in the present study after eosinophils were exposed to S. stercoralis antigens.…”
Section: Discussionsupporting
confidence: 64%
“…One of the activating agents produced by endothelial cells is platelet-activating factor (PAF) [11]. The increase of CD11b expression and concomitant shedding of L-selectin is not only observed in vitro [12,13]; a number of studies have shown increased Mac-1 expression and decreased L-selectin expression on extravasated neutrophils and eosinophils in vivo [2,14,15].…”
mentioning
confidence: 99%